Lybia - Amaral, Inês (2013)
The history of Libya is parallel to that of other once-colonized nations. Therefore, it displays economic, class, gender, religious, and ethnic inequalities. Libya gained independence from Italy in 1951. The country became The United Kingdom of Libya, a constitutional and hereditary monarchy. After the discovery of oil reserves and a large income from petroleum sales, Libya established as a wealthy nation. However, discontent arises with the concentration of the country’s wealth in the power sphere.